2001
DOI: 10.1080/15216540152846028
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Calcium Homeostasis: Mechanisms and Molecules

Abstract: SummaryDespite the early characterisation of Ca 2+ uxes in isolated mitochondria and the ability of this ion to up-regulate dehydrogenases of the Krebs cycle, the low af nity of the organelle uptake pathways was a long-standing obstacle to the recognition of a physiological role for mitochondrial Ca 2+ uptake. This review begins with a historical account of the main results that proved the contrary and provides a brief description of mitochondrial Ca 2+ signals. Then, it discusses the characteristics of Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 59 publications
(101 reference statements)
0
39
0
Order By: Relevance
“…Sustained Ca 2ϩ release from the ER can trigger Ca 2ϩ uptake by the mitochondria (26,36). The mitochondria possess an exceptional capacity to sequester Ca 2ϩ and buffer local variations in [Ca 2ϩ ] c levels via the activity of electrophoretic uniporters localized in the inner membrane (26,37). The close proximity of the mitochondria to the ER is believed to facilitate this process, which is possibly mediated via ER-mitochondria contact sites (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustained Ca 2ϩ release from the ER can trigger Ca 2ϩ uptake by the mitochondria (26,36). The mitochondria possess an exceptional capacity to sequester Ca 2ϩ and buffer local variations in [Ca 2ϩ ] c levels via the activity of electrophoretic uniporters localized in the inner membrane (26,37). The close proximity of the mitochondria to the ER is believed to facilitate this process, which is possibly mediated via ER-mitochondria contact sites (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria possess an exceptional capacity to sequester Ca 2ϩ and buffer local variations in [Ca 2ϩ ] c levels via the activity of electrophoretic uniporters localized in the inner membrane (26,37). The close proximity of the mitochondria to the ER is believed to facilitate this process, which is possibly mediated via ER-mitochondria contact sites (37,38). Mitochondrial Ca 2ϩ uptake has long been known to stimulate the turnover of matrix dehydrogenases coupled to the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria play key roles in the maintenance of Ca 2+ ion homeostasis (Vandecasteele et al, 2001), and studies have shown that MF dynamics are important for the arrangement, distribution, and function of mitochondria (Vandecasteele et al, 2001). Mitochondria move along MFs and function as Ca 2+ stores in plant cells (Vandecasteele et al, 2001;Wang et al, 2004a), and stress induces mitochondrial-mediated cell death processes in plants (Yao et al, 2004;Lin et al, 2005;Gao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Following intracellular Ca 2+ elevation, mitochondria rapidly take up and accumulate Ca 2+ to maintain cellular Ca 2+ homeostasis (12). Studies also have shown that Ca 2+ uptake into mitochondria occurs through the mitochondrial Ca 2+ uniporter (12,13), and that mitochondrial Ca 2+ influx can increase ATP production by activating the TCA cycle, as well as enhance the activities of the electron transportchain enzymes and the ATP synthase complex (14)(15)(16)(17). Nevertheless, the relationship between mitochondrial energetic status and mitochondrial movement remains controversial.…”
mentioning
confidence: 99%